An Epidemiological Exploration of Binge Eating Disorder and Its Emotional Roots among Youth in Greater Jakarta - Kurniati, Henny; Asy'ari, Yudha; Helmi, Tri Amelia Rahmitha; Sundjaya, Tonny (UI Scholars Hub, 2025)
The rising prevalence of mental disorders among youth, including depression, anxiety, stress, and binge eating disorder (BED), has become a major concern in the context of global mental health. BED, as a form of eating disorder, often occurs with psychological conditions such as anxiety and depression, complicating diagnosis and treatment. This study aimed to investigate the prevalence and association between depression, anxiety, stress, and BED among youth in Greater Jakarta. Using a cross-sectional online design, data were collected from 231 participants aged 18-25 years through the Binge Eating Scale (BES) and Depression Anxiety Stress Scale-21 (DASS-21). Statistical analysis involved bivariate testing and logistic regression to identify risk factors and association among variables. This study indicated that BED prevalence was higher among female respondents and individuals with a BMI ≥25. Anxiety emerged as the primary factor increasing the risk of BED by up to four times, while stress was not a significant predictor. These findings emphasized the importance of early detection and psychological interventions, as well as preventive approaches such as routine screening and improved access to mental health services for youth. In conclusion, anxiety and obesity were key factors that need comprehensive management to reduce BED occurrence and enhance adolescent mental health. Keywords : Anxiety, Binge Eating Disorder, Depression, Stress, Youth